2019
DOI: 10.1177/1947603519888793
|View full text |Cite
|
Sign up to set email alerts
|

Automated Knee Osteoarthritis Assessment Increases Physicians’ Agreement Rate and Accuracy: Data from the Osteoarthritis Initiative

Abstract: Objective. To assess the impact of a computerized system on physicians’ accuracy and agreement rate, as compared with unaided diagnosis. Methods. A set of 124 unilateral knee radiographs from the Osteoarthritis Initiative (OAI) study were analyzed by a computerized method with regard to Kellgren-Lawrence (KL) grade, as well as joint space narrowing, osteophytes, and sclerosis Osteoarthritis Research Society International (OARSI) grades. Physicians scored all images, with regard to osteophytes, sclerosis, joint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 22 publications
4
21
0
Order By: Relevance
“…6 Several additional studies have shown that automated quantification of nodules, bone age prediction, and knee assessment (eg, osteoarthritis) can help reduce radiologists' workload and improve diagnosis accuracy. [7][8][9] Additionally, AI-based applications may improve image interpretation in differentiating lung viruses such as COVID-19 from other pneumonia diseases. 10,11 It remains to be seen whether AI will aid radiographers in clinical decision-making, such as scanning protocols or radiation doses.…”
Section: Introductionmentioning
confidence: 99%
“…6 Several additional studies have shown that automated quantification of nodules, bone age prediction, and knee assessment (eg, osteoarthritis) can help reduce radiologists' workload and improve diagnosis accuracy. [7][8][9] Additionally, AI-based applications may improve image interpretation in differentiating lung viruses such as COVID-19 from other pneumonia diseases. 10,11 It remains to be seen whether AI will aid radiographers in clinical decision-making, such as scanning protocols or radiation doses.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been shown that bone or vessel suppression on thorax imaging can elevate the detection of lung nodules (level 3) [20,37]. In the area of musculoskeletal radiology, we found that automated knee assessment might improve both the agreement between physicians and the accuracy of the osteoarthritis diagnosis (level 3) [38].…”
Section: Improved Diagnostic Accuracymentioning
confidence: 69%
“…Although promising, the analysis of such heterogeneous aspects could seem challenging with the current technologies, but the emerging advances in machine learning protocols may open a completely new horizon for a multidimensional evaluation of OA patients. 185…”
Section: Discussionmentioning
confidence: 99%